Konsep Diri terhadap Proaktif Koping pada Mahasiswa yang sedang Menyusun Skripsi - Rahmad, La ode Alwahab; Abas, Muhammadd; Marhan, Citra (Jurusan Psikologi FKIP Universitas Halu Oleo, 2024)
Students with low proactive coping tend to be unable to overcome conflicts and obstacles that are encountered daily, including those related to academics such as skipping. On the contrary, students with high proactive coping tend to be able to overcome conflicts and obstacles that are encountered daily. Self-concept is one way to improve proactive coping. Therefore, this research was conducted with the aim of knowing the relationship between self-concept and proactive coping in students who are preparing their thesis. The sampling technique used cluster random sampling, so that a total sample of 100 people was obtained from 2,062 student populations who were preparing their thesis at the Faculty of Teaching and Education, Halu Oleo University. The data collection method uses a self-concept scale and a proactive coping scale. The data analysis technique uses the Pearson's Product Moment correlation method. The research results obtained showed that there was a positive relationship between self-concept and proactive coping in students who were preparing their thesis.